Akulturasi Budaya dalam Arsitektur Klenteng Sam Poo Kong Semarang: Kajian Estetika Visual dan Nilai Historis sebagai Warisan Multikultural - Desti Syahara; Riski Kurnia (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
The lack of public understanding of the cultural and historical values contained in multicultural worship buildings. Sam Poo Kong Temple in Semarang is an important object to study cultural acculturation reflected in its architecture, visual aesthetics, and historical values. This research aims to reveal how the combination of Chinese, Javanese and Islamic elements is reflected in the physical and symbolic forms of the temple. The method used is descriptive-analytical qualitative through direct observation, visual documentation, interviews, and literature study. The analysis was done thematically with architectural aesthetics and visual semiotics approaches. The results show that Sam Poo Kong Temple not only functions as a place of worship, but also as a symbol of tolerance and multicultural identity. The combination of ornaments, colors, structures, and symbols represent the values of togetherness, spirituality, and cross-cultural heritage. This temple plays an important role in strengthening social cohesion and becoming a cultural asset that supports the development of an inclusive and harmonious society.